Donation Intention and Behavior in Indonesian Digital Crowdfunding: Integrating Social Presence and Interpersonal Behavior Theories - Budi Sukardi; Rizky Nur Ayuningtyas Putri; Rahmat Hidayat; Fuad Dhiya Ul Husaen (SCAD Independent, 2026)
The rapid digitalization of Islamic social finance has transformed philanthropic practices, particularly through digital crowdfunding platforms that mediate zakah, infaq, sadaqah, and waqf donations. Despite technological advancement, donor participation in digital channels remains uneven, indicating a persistent gap between intention and actual donation behavior. This study examines the determinants of donation intention and behavior on Indonesian digital crowdfunding platforms by integrating the Theory of Interpersonal Behavior (TIB) and Social Presence Theory (SPT). Using a quantitative cross-sectional survey of 440 active donors across four major Indonesian cities and analyzing the data with SEM-PLS, the study investigates the roles of motivational, relational, and contextual factors. The findings show that attitude, affection, social factors, and religiosity significantly influence donation intention, while intention and trust are the primary drivers of actual donation behavior. Social presence, facilitating conditions, and habits do not exert direct effects on behavior; however, facilitating conditions significantly strengthen the intention–behavior relationship. These results highlight that digital donation behavior is shaped not only by technological access but also by emotional engagement, social embeddedness, and institutional trust. By clarifying the moderating role of facilitating conditions, this study contributes to a more comprehensive understanding of digital philanthropy and offers insights for developing sustainable, trustworthy, and context-sensitive crowdfunding platforms in Muslim-majority societies.